Fermentasi Batang Pisang Sepatu (Musa Paradisiaca Forma Typica) Terhadap Palatabilitas Sapi Bali (Bos Sondaicus) - Rahmat Anwar; Umbang Arif Rokhayati (Jambura Journal of Animal Science, 2020)
This study aims to determine the palatability of Balinese cattle to the silage of banana shoe stems. The study was conducted in March to April 2019 in Dambalo Village, Tomilito Subdistrict, North Gorontalo Regency. The research site had a capacity of 50 cattle but this study used 20 cows which were divided into 2 groups. The first group as control was given 15 kg of elephant grass and then added 1 kg / head / day of fresh banana feed and the second group was given 15 kg of elephant grass and 1 kg / head / day of banana shoe silage feed treatment. While processing data using the t test. The results showed that banana shoe stem silage feed was significantly different (P 0.05) to the value of palatability or preferred by Balinese cattle. Whereas the value of body weight gain is higher in cattle given banana silage feed compared to Balinese cattle which are fed fresh banana stems, where the average weight gain of Bali cattle is 42 to 57 grams / head / day. The conclusion is that the treatment of banana shoe stem fermentation was significantly different (P 0.05) to the palatability of Balinese cattle.